Planning your dream home safely: Understanding Regulations and Avoiding Public Housing Savings Breaches - Salabay, Rosita; Watofa, Yohana; Mansawan, Isak (Sinergi International Journal of Law, 2024)
The reality is that having a decent home is still the dream of most people, especially those with middle to lower income. The scarcity between the need and availability of houses is still an unresolved problem, so access to decent and affordable housing is still very limited. This study investigates Government Regulation Number 25 of 2020 and Law Number 4 of 2016, which respectively regulate the operation of the Public Housing Savings Fund (Tapera). The purpose of this study is to understand the Tapera regulations and identify administrative violations that may occur. This research method uses a descriptive approach to understand regulations and identify forms of administrative violations and sanctions in the implementation of Tapera. The results show that to ensure the continuity of the program, the management of Tapera funds must be carried out in a transparent and accountable manner. The government and financial institutions must ensure that fund management is carried out with high transparency and accountability. Administrative sanctions imposed for violations of the provisions of this law are very important to ensure the stability and sustainability of the Tapera program.